Editorial do WIE 2025 - Valle, Pedro Henrique; Bim, Silvia Amélia; Pereira Júnior, Cleon Xavier; Pereira, Roberto (Anais do Workshop de Informática na Escola (WIE), 2025)
Este documento traz os elementos pré-textuais e comitês do WIE 2025.